Предмет: Математика,
автор: Arushant
Упростите выражение: (x/x^2+2x+4+x^2+8/x^3-8-1/x-2)*(x^2/x^2-4-2/2-x)
Приложения:
Ответы
Автор ответа:
4
Ответ:
Пошаговое объяснение:
1)((х-2)х+х^2+8-х^2-2х-4)/(х^2-8)=
(Х^2-2х+х^2+8-х^2-2х-4)/(х^2-8)=
(Х^2-4х-4)/(х-2)(х^2+2х+4)=
(х-2)^2/(х-2)(х^2+2х+4)=
(Х-2)/(х^2+2х+4)
2)х^2/(х-2)(х+2)-2/(2-х)=х^2/(х-2)(х+2)+
2/(х-2)=х^2+2(х+2)/(х+2)(х-2)=
(Х^2+2х+4)/(х-2)(х+2)
3)(х-2)/(х^2+2х+4)×(х^2+2х+4)/(х-2)(х+2)=1/(х+2)
Похожие вопросы
Предмет: Геометрия,
автор: vasapybkin
Предмет: Английский язык,
автор: Аноним
Предмет: Геометрия,
автор: tanyanel12345
Предмет: Биология,
автор: Navitel1
Предмет: Математика,
автор: Olgakazakova2